DIFFERENTIATED TEACHING METHOD FROM THE STUDENTS ABILITY IN READING COMPREHENSION AT SMAN 4 KEDIRI - Nila Nisaul Hasanah; Yunik Susanti; Diani Nurhajati (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
The development of the times has provided changes in the world of education which are marked by changes in curriculum policies according to the needs of the times. In the 2022 the Ministry of Education and Culture issued a new curriculum called Merdeka Curriculum. One of the appropriate learning methods for Merdeka Curriculum is differentiated teaching method. Concern for students by paying attention to strengths and needs is the focus in differentiated teaching. The purpose of this research is to find out how the effect of differentiated teaching on students’ reading comprehension skills. In this study, researcher used a quantitative approach with research subjects in class X11 at SMAN 4 Kediri. The method used in this research is a one group pre-test post-test design. Researcher collected data through the scores of students’ pre-test post-test design. The results of the t test hypothesis test obtained t count > t table, namely 10,723 > 1,690, based on the hypothesis testing criteria then H0 is rejected. This shows that there is a significant effect of differentiated teaching on students’ reading comprehension. The researcher suggests to English teachers that using differentiated teaching through students’ abilities is more effective because this method is suitable for improving students’ reading comprehension skills.